Evaluation of the chemical control of bacterial leaf blight (Xanthomonas oryzae pv. oryzae) of rice in transplanted rice (Oryza sativa L.) crop - Asghar, Muhammad; Hussian, Muzammal; Ahmad, Iftekhar; Talfoor-ul Hasan; Iqbal, Mazhar Faid; Mahdi, Muhammad Montazir; Ali, Muhammad Anjum (Journal of Pure and Applied Agriculture, 2023)
Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. Oryzae is considered a major threat to rice production worldwide including in Pakistan. Thus field trials were conducted to evaluate different commercially available antibacterial chemicals against this destructive disease on the rice cultivar Pk-386. For this purpose, comparative efficacy of bleaching powder, Kasumin 2SL (kasugamycin), Triseen 5SL (validamycin), Profile 50WP (kasugamycine+copperoxychloride), Coopix 50WP (copper oxychloride) Thrill 20WP (bismerthiazole) was studied as foliar spray applications against BLB at their recommended doses. The experiment was laid out in randomized complete block design with three replications. Among the tested chemicals the disease incidence (60.44%), Disease severity index (16.79% ) were the lowest for Coopix 50WP with the highest yield (6.58 tonnes ha-1 ) followed by Profile 50WP with 78.56%, 21.96%, and 6.44 tonnes ha-1 respectively. The performance of the control plot as compared to other treatments remained poor with the highest (98.08%) disease incidence, 58.01% (disease severity index) and lowest yield 50.67 tonnes ha-1 . The benefit to cost ratio in cases of Coopix 50WP and bleaching powder was same (1:13) but the incremental increase in income over the control with Coopix 50WP was highest (Rs. 30330) as compared to that of (Rs.16352) with the use of bleaching powder. Therefore on the basis of results copper oxychloride and kasugamycine+copper oxychloride could be recommended for the economic and efficient control of bacterial leaf blight of rice crops. © 2022 Department of Agricultural Sciences, AIOU